2015
DOI: 10.1371/journal.pone.0131994
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nevirapine Resistance in Children Exposed to the Prevention of Mother-to-Child HIV-1 Transmission Programme in Maputo, Mozambique

Abstract: BackgroundSingle-dose nevirapine (sd-NVP) has been the main option for prevention of mother-to-child transmission (PMTCT) of HIV-1 in low-resource settings. However, sd-NVP can induce the selection of HIV-1 resistant mutations in mothers and infants. In Mozambique, there are limited data regarding the profile of NVP resistance associated mutations (RAM) in the context of PMTCT.ObjectivesTo assess the prevalence and the factors associated with NVP RAM among children born to HIV-1 infected mothers enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Higher virologic suppression rates have been reported while on second-line PI regimens compared to second-line NNRTI regimens (80% vs. 25%; p=0.009), 19 reflecting the potency of boosted PI regimens and the reduced risk of archived mutations compared to NNRTIs. 20,21 Although the majority of our patients remained virologically suppressed throughout the study period, 27% developed at least one episode of VF during the study monitoring period. We observed that 55% of those with an initial elevated viral load had persistent VF for 24 weeks (two consecutive measurements) and 32% had persistent VF for 48 weeks (three consecutive measurements).…”
Section: Discussionmentioning
confidence: 80%
“…Higher virologic suppression rates have been reported while on second-line PI regimens compared to second-line NNRTI regimens (80% vs. 25%; p=0.009), 19 reflecting the potency of boosted PI regimens and the reduced risk of archived mutations compared to NNRTIs. 20,21 Although the majority of our patients remained virologically suppressed throughout the study period, 27% developed at least one episode of VF during the study monitoring period. We observed that 55% of those with an initial elevated viral load had persistent VF for 24 weeks (two consecutive measurements) and 32% had persistent VF for 48 weeks (three consecutive measurements).…”
Section: Discussionmentioning
confidence: 80%
“…Poor adherence and mutation can lead to drug resistance [16]. Although our study didn’t include sequencing of the genetic material, some studies revealed that NVP had a high rate of resistance to HIV among infants [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Single-point mutations confer resistance to nevirapine and are known to be selected in almost all exposed even to a single dose of this drug. 25,26 Infants were transitioned to lopinavir/ritonavir at 42 weeks post menstrual age but this drug is known to present significant adherence challenges due to poor palatability. Better formulations of antiretroviral drugs with better tolerability and simplified dosing for this age group is an urgent research priority.…”
Section: Discussionmentioning
confidence: 99%